Word Formation in Tempo English Articles Following the Indonesian Military Law Amendments Passing - fadilah, fadilah; Yuni Indriyanti (Pujangga, 2025)
This study aims to analyze the types and frequency of word formation processes found in Tempo’s national English articles following the passing of the Indonesian Military Law amendments. This research employs a descriptive qualitative method using George Yule’s (2023) theory of word formation as the main framework. The data consist of five online national news articles published by Tempo between March 20th and March 27th, 2025. The analysis reveals that six types of word formation processes appear in the articles, namely borrowing, derivation, multiple processes, compounding, conversion, and initialism. Borrowing is found to be the most dominant type with 11 data, followed by 7 data as derivation, 3 data as multiple processes, 2 data as compounding, 2 data as conversion, and 1 data as initialism. The findings show that borrowing plays a significant role as the most productive word formation process in the articles, indicating that many English words used in news media come from other languages. Moreover, the study highlights that not all word formation types consistently appear, and a few words could not be categorized into any existing morphological process. These findings underline the importance of borrowing in shaping the English vocabulary in Indonesian journalistic contexts.